Bureaucracy intermediaries, corruption and red tape - Anders Fredriksson (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2010)
Intermediaries helping individuals and firms with the government bureaucracy are common in developing countries. Although such bureaucracy intermediaries are, anecdotally, linked with corruption and welfare losses, few formal analyses exist. In our model, a government license can benefit individuals. We study individuals' net gain when acquiring the license through the regular bureaucratic procedure, through bribing or through intermediaries. For a given procedure, individuals using intermediaries are better off than if intermediaries and corruption had not existed. Intermediaries "grease the wheels". We then study incentives of corrupt bureaucrats to create red tape. When free to choose levels of red tape, bureaucrats implement more red tape and individuals are unambiguously worse off in a setting with intermediaries than with "direct" corruption only. Intermediaries can thus improve access to the bureaucracy, but also strengthen incentives to create red tape - a potential explanation why license procedures tend to be long in developing countries.
Keywords: D73; O12; 330; Bureaucracy; Corruption; Intermediaries; Red tape